ICT Based Innovation in Tourism Marketing (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Impact is not created by big budgets; it is created by innovative marketing approaches. An  innovation is nothing but it is viewed as anything new that solves needs by offering significant  advantages like adding up extra features, more convenience, being user friendly and most  importantly being cost efficient. In order to generate more profits from the customer new products  or services are being floated in the market. The need for innovation is not hold-up to product  industry it also has an immense importance in service industry as well.  In India, Tourism is the largest service industry; it is one of the major sources of economic  growth in India. After independence, the focus of development in India was on key areas like  agriculture, housing, industry, irrigation, infrastructure and other social sectors. Tourism in  India has been a late starter and has started getting attention in the last two decades only and  with so many marketing innovation techniques it has made a remarkable impact on world map.  The role of ICT in Tourism industry cannot be ignored in current information driven society. It has  provided new tools and enabled new distribution channels, thus creating a new business  environment.
Keywords: ICT; Innovation; Tourism & Marketing